A Comparison of the Bilateral Axillo-breast Approach (BABA) Robotic and Open Thyroidectomy for Papillary Thyroid Cancer After Propensity Score Matching. Issue 5 (25th October 2022) - Paek, Se Hyun; Kwon, Hyungju; Kang, Kyung Ho
Abstract : Background: We aimed to investigate the potential advantages of bilateral axillo-breast approach (BABA) robotic thyroidectomy over conventional open surgery and to determine whether it is a safe and complete surgical procedure compared with open surgery in patients with papillary thyroid cancer. Patients and Methods: We retrospectively reviewed the records of 315 consecutive patients (robotic, n=54; open, n=261) who underwent total thyroidectomy and central neck dissection for papillary thyroid cancer from March 2013 to June 2014. Postoperative complication rate and surgical completeness were analyzed between patients who underwent BABA robotic thyroidectomy (robotic group) and those who chose open thyroidectomy (open group) after propensity score matching according to age, sex, body mass index, tumor size, extrathyroidal extension, and lymph node (LN) metastasis. Results: Transient hypoparathyroidism was higher in the open group than in the robotic group (13.0% vs. 1.9%; P =0.029). No difference was observed in the mean number of retrieved LNs and metastatic LNs. The mean level of stimulated thyroglobulin was acceptably low in both groups, and there was no difference in the proportion of patients who had stimulated thyroglobulin levels <1 ng/mL between the groups ( P =0.543). Conclusions: Our results show that the outcomes of BABA robotic thyroidectomy may be comparable to those of conventional open thyroidectomy, with possibly better preservation of blood supply to the parathyroid glands, without sacrificing surgical completeness.